Angioscopic comparison of arterial repair after second-generation drug-eluting stent implantation into vulnerable and stable coronary plaques. (15th October 2016) - Kawai, Kenji; Ichikawa, Minoru; Masuyama, Tohru; Kijima, Yoshiyuki
Abstract: Background: Arterial repair after intracoronary stenting depends on stent types and plaque vulnerability. The aim of this study was angioscopic comparison of arterial repair after implantation of the second-generation drug-eluting stents (G2-DES) between the stable and vulnerable plaques. Methods: Four types of G2-DES were successfully implanted into stable plaques (n = 41) and vulnerable plaques (n = 34): 13 and 9 Xience-everolimus-, 7 and 6 Endeavor-zotarolimus-, 15 and 9 Resolute-zotarolimus-, and 6 and 10 Nobori-biolimus-eluting stents (EES, E-ZES, R-ZES, and BES), respectively. Coronary angioscopy at 1-year follow-up revealed in-stent appearance, such as neointimal stent coverage (NSC), presence of yellow plaques (YP), and in-stent mural thrombus (MT). NSC was graded into poor and good coverage. Results: Yellow plaques and mural thrombi were found more frequently in the vulnerable plaques than in the stable plaques (29% vs. 12%, P = 0.06; 12 vs. 0%, P = 0.02; respectively). In EES, poor NSC was observed more frequently in the vulnerable plaques than in the stable plaques (54% vs. 11%, P = 0.04). In BES, YP was observed more frequently in the vulnerable plaques than in the stable plaques (80% vs. 17%, P = 0.01). In E-ZES and R-ZES, there were no significant differences with regards to angioscopic parameters between the stable and vulnerable plaques. Conclusions: Arterial repair after EES and BES implantation into the vulnerable plaques remained vulnerable even at 1-year follow-up.